(untitled) (Journal of Population and Development, 2021)
Eco-criticism examines the conflicting relationship between man and nature. Human beings encroach nature for their comfort and material prosperity. Nature is silent but it may crush us if we go against it crossing the limit. It is the holistic environmental theory, according to which not only living beings, but the whole ecosystem, including the biotic part of nature, is worthy of moral consideration. This paper examines how so called mechanical world i.e. physical world comes into tussle with the natural world in the poems-“Travelling through the Dark” and “Woodchucks”. This mundane world is the world of scientific inventions and machines. Human beings have become the slaves of machines and tools. They heavily depend on machinery objects to ease and comfort their life. But sometimes they misuse the machines and damage the natural objects posing threat to natural ecosystem. In ecosystem, all living beings- plants and animals are equally important as they are interdependent for their existence. If one of the animals is exterminated, other living beings in an ecosystem will be badly affected. This paper examines how the conflict between nature and modern technology occurs in the poems: “Travelling through the Dark” by William Stafford and “Woodchucks” by Maxine Kumin. This paper uses eco-criticism as a theoretical frame work for the research study. It compares and contrasts between two poems in terms of the nature of conflict between nature and modern technology. It answers the questions: How do human beings misuse the objects of the mechanical world at the risk of the natural world? Since natural eco-system is an integral part of our life, we need to conserve it for the safety of our own existence.